The Effect Of Counselling With Demonstration Methods On Tooth Brushing Skills In Students Sdn 1 Lampeuneurut Aceh Besar - Mufizarni; Farsia, Lina; Hanum, Cut fazlil; reca, reca (Journal Dental Health, 2023)
Good and correct tooth brushing skills in children are very necessary in maintaining oral hygiene as an effort to prevent oral health problems. The biggest dental problems occur in children because they do not know how to maintain oral health. Brushing teeth is an activity to clean teeth from food debris, plaque and bacteria. The purpose of this study was to determine the effect of counselling with the demonstration method on tooth brushing skills in students of SDN 1 Lampeuneurut Aceh Besar. The research method used is quantitative research method using pre-experimental design type one group pretest-posttest method.  The population in this study were all students of class IV and V SDN 1 lampeuneurut Aceh Besar. The sample in this study amounted to 50 respondents. The analysis conducted was univariate and bivariate analysis with T-Test statistical test. The results of the research before and after (pre-post) using the Paired Sample T-Test Test obtained a p value of 0.001 or p < 0.05. In the pre-test results, respondents who had good brushing skills were 12 people (24%), and respondents who had poor brushing skills were 38 (76%). After being given counselling with the demonstration method, it was found that there was a significant increase in tooth brushing skills in SDN 1 Lampeuneurut Aceh Besar students, namely most respondents had good tooth brushing skills as many as 37 people (74%) and those who had poor tooth brushing skills were 13 people (26%). Based on the results of the study it can be concluded that there is an effect of counselling with the demonstration method on tooth brushing skills in students of SDN 1 Lampeuneurut Aceh Besar. It is recommended to students to maintain their oral health and to other related parties in order to provide counselling and information about maintaining proper dental health in school children.